Posttransfusion purpura occurrence and potential risk factors among the inpatient US elderly, as recorded in large Medicare databases during 2011 through 2012. Issue 2 (28th July 2014) - Menis, Mikhail; Forshee, Richard A.; Anderson, Steven A.; McKean, Stephen; Gondalia, Rahul; Warnock, Rob; Johnson, Chris; Mintz, Paul D.; Worrall, Christopher M.; Kelman, Jeffrey A.; Izurieta, Hector S.
<x xml:space="preserve">Abstract</x> Background Posttransfusion purpura (PTP) is a serious transfusion complication resulting in sudden thrombocytopenia with bleeding. The study's objective was to assess PTP occurrence and potential risk factors among the inpatient US elderly, ages 65 and older, during 2011 through 2012. Study Design and Methods This retrospective claims‐based study utilized large Medicare databases for calendar years 2011 and 2012. Transfusions of blood and blood components were identified by recorded ICD‐9‐CM procedure codes and revenue center codes, and PTP was ascertained via ICD‐9‐CM diagnosis code. Our study evaluated PTP rates (per 100, 000 inpatient transfusion stays) among elderly Medicare beneficiaries, overall and by age, sex, race, number of units, and blood components transfused. Multivariate regression analyses were used to assess potential risk factors. Results Among 4, 336, 338 inpatient transfusion stays for elderly beneficiaries during the study period, 78 had a PTP diagnosis code recorded, an overall rate of 1.8 per 100, 000 stays. PTP occurrence varied by the blood components, units transfused, and other characteristics. Significantly higher odds of PTP were found for platelet (PLT)‐containing transfusions, with greater number of units transfused, as well as for elderly with histories of cardiac arrhythmias (odds ratio [OR], 2.65; 95% confidence interval [CI], 1.43‐4.93), coagulopathy (OR, 1.79; 95% CI, 1.01‐3.21), leukemia (OR, 2.37; 95% CI, 1.07‐5.26), transplant (OR, 2.68; 95% CI, 1.41‐5.09), and other conditions. Conclusion Our population‐based study suggests a substantially higher PTP risk with PLT‐containing transfusions. The study also suggests increased PTP risk with greater number of units transfused as well as the importance of underlying health conditions and prior recipient alloimmunization for PTP occurrence among the elderly.